2020
DOI: 10.56239/rhcs.2020.64.448
|View full text |Cite
|
Sign up to set email alerts
|

Ideas erróneas sobre el COVID-19: una encuesta transversal en línea, Costa Rica, 2020.

Abstract: El mundo enfrenta desde hace casi un año la pandemia por el virus SARS Cov-2 (COVID-19), exigiendo con el transcurrir del tiempo mayores respuestas de salud pública y de educación para la salud para controlarla y mitigar los daños en la salud de las personas. Existe una gran cantidad de información en internet; sin embargo, no toda la información disponible procede de fuentes académicas, ni mucho menos posee la solidez y veracidad, conllevando a gran desinformación. Se realizó un estudio transversal en línea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…In regard to educational level, it was found that those with a higher or postgraduate level of education had a better level of knowledge compared to those with only a primary or a lower level. This result is similar to what was reported by multiple studies, in which a better education level was associated with having correct ideas about COVID-19 ( 22 24 ). Therefore, governments and authorities should intensify information dissemination campaigns in the population with primary or lower educational levels, as well as implement measures to reduce the dissemination of false information.…”
Section: Discussionsupporting
confidence: 92%
“…In regard to educational level, it was found that those with a higher or postgraduate level of education had a better level of knowledge compared to those with only a primary or a lower level. This result is similar to what was reported by multiple studies, in which a better education level was associated with having correct ideas about COVID-19 ( 22 24 ). Therefore, governments and authorities should intensify information dissemination campaigns in the population with primary or lower educational levels, as well as implement measures to reduce the dissemination of false information.…”
Section: Discussionsupporting
confidence: 92%
“…En las redes neuronales convolucionales (CNN), sé ha usado la función de activación ReLU, cuya función es la de aumentar la propiedad no lineal de activación sin que se modifiquen los cuerpos receptivos de dichas capas convolucionales [17].…”
Section: E Los Modelos De ML Usadosunclassified